Determinants of Human Papilloma Virus (HPV) Vaccination among Elementary Students in Central Jakarta - Febrianti, Rini; Wahidin, Mugi (Indonesian Journal of Cancer, 2021)
Background: Human Papilloma Virus (HPV) is the leading risk factor of cervical cancer. World Health Organization (WHO) has recommended including HPV vaccination in national immunization programs in all countries. Specifically, Jakarta Province has been implementing HPV vaccination since 2016. In this case, several factors influence vaccination coverage. However, there is limited evidence about determinants associated with HPV vaccination. Therefore, this study aimed to investigate the factors associated with HPV vaccination among elementary students in Central Jakarta.Methods: This was a cross-sectional study conducted from March until June 2020. The study population involved 167 female students of the 6th level of the elementary school in Central Jakarta. There were eight elementary schools in Kemayoran and Cempaka Putih Sub Districts selected purposively. Primary data was collected employing an online questionnaire, which was fulfilled by respondents (mothers and students). Data were analyzed utilizing statistic software for descriptive and bivariate analysis. For the bivariate analysis, Chi-Square Test was performed.Results: The HPV vaccination coverage was 80.84%. It was also showed that the last education level of the respondents’ father and mother was mainly senior high school (SMA) for 50.3% and 47.9%, respectively. The mothers’ knowledge was mainly in the middle (56.9%), and they had a positive attitude/support (67.1%). There were only 2.4% of the respondents with a family history of cervical cancer. In terms of family economic status, the main part of respondents had low expenditure for 2-3 million IDR (59.3%) a month. Meanwhile, human resources (vaccination providers) and HPV vaccine were 100% available in the vaccination service. Of the respondent, 47.9% of those said that the vaccine price was affordable. Children who had no support to get HPV vaccination from their father, mother, and siblings were 14.4%, 6.6%, and 21.6%, respectively. Besides, children who were not supported by their teachers was 3.6% and not supported by their peers was 23.4%. Meanwhile, father and mother’s supports were significantly associated with HPV vaccination.Conclusions: Factors associated with HPV vaccination were the support from the father and mother.